Case Report: Virus-induced rhabdomyolysis ranging from mild course to acute renal injury, hyperferritinemia and poor outcome: a case series of four pediatric patients - van der Zee, Carlijn W.; Biesbroek, Giske; Oosterveld, Michiel J. S.; Koot, Bart G. P.; Schoenmaker, Nikki J.; Kuijpers, Taco W. (Frontiers in Pediatrics, 2025)
We report a case-series of four healthy pediatric patients presenting with virus-induced rhabdomyolysis. Rhabdomyolysis is characterized by rapid breakdown of skeletal muscle, which can result in mild complications to acute kidney injury and even death. In children rhabdomyolysis is often virus-induced. In this case series we describe two pediatric patients with severe complications, including acute kidney injury, hyperferritinemia and even in one case liver failure and death. The rhabdomyolysis in the other two patients was caused by different viruses and had a milder presentation and good outcome after hyperhydration. Our cases highlight the variability in clinical outcome in virus-induced rhabdomyolysis. The outcome of our cases may suggest that hyperferritinemia can play a critical role in the pathophysiology of acute kidney injury and therefore may be used as an important biomarker for disease severity.